If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 6) = 6(x + -6) + x Reorder the terms: 7(6 + x) = 6(x + -6) + x (6 * 7 + x * 7) = 6(x + -6) + x (42 + 7x) = 6(x + -6) + x Reorder the terms: 42 + 7x = 6(-6 + x) + x 42 + 7x = (-6 * 6 + x * 6) + x 42 + 7x = (-36 + 6x) + x Combine like terms: 6x + x = 7x 42 + 7x = -36 + 7x Add '-7x' to each side of the equation. 42 + 7x + -7x = -36 + 7x + -7x Combine like terms: 7x + -7x = 0 42 + 0 = -36 + 7x + -7x 42 = -36 + 7x + -7x Combine like terms: 7x + -7x = 0 42 = -36 + 0 42 = -36 Solving 42 = -36 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 45b-15=45b+45 | | ((x^3)-27)=0 | | 7(x+3)+5(x+3)=5x-5 | | 460=91x+x | | 45b-15=40b+45 | | x^2-2x+20=0 | | 10k+7=-3-10k | | 40b-15=40b+45 | | 2a-(1-a)=11 | | x+7x=180 | | 4p+10=2p+16 | | 3(2x-5)=24x | | 12y-3xy=18 | | 2x+4=6(2x+4) | | -8-3x=-4x+1 | | x+(2x+0.15)+(x+0.05)=18 | | x^2+19x+266=0 | | (x-5)+(3x^2)=y | | 19m=6+3m | | 3x+7(3x-3)=9-6x | | 23(4x-4x)=2-5 | | 1+(-4(x^2))=0 | | 7x^2-27x+18=0 | | 6-x=2x+16 | | 2(3-x)(4x-9)=0 | | .6x^2-2.4x-.6=0 | | y=x-7is | | 3(x+1)=x-21 | | 36-4b=4(-b+3) | | 36-4b=4b(-b+3) | | 40v+7=90v+30 | | 2(x+1)(x+5)-10=0 |